Factors Causing Incorrect External Cause Code In Accident Cases In General Hospital Mitra Medika In 2022 - Marta Simanjuntak; Esraida Simanjuntak; Siti Permata Sari Lubis; Nurhalimah Nasution (Sean Institute, 2023)
The external cause code is the code used to classify the external causes of a disease whether caused by accidents, injuries, burns, poisoning, side effects or other causes. The purpose of this study is to find out what are the factors causing the inaccuracy of the external cause code in accident cases at Mitra Medika General Hospital and how the procedure for coding the external cause code is carried out at the hospital. The type of research used is quantitative. The number of samples in this study were 4 coder officers and 32 medical record file forms with a percentage of 25% incomplete and 75% completely filled out. SOPs for disease codes and actions already exist, however, there is still no SOP for external cause cases in detail. Coding is carried out by coding officers with a background in D3 Medical Records who are guided by SOPs using ICD-10 of 2010 electronically and then entered into the INA-CBGs. The method of coding is done by first looking at ICD-10 Volume 3 and then confirming again on ICD-10 Volume 1. Chronological information on external cause events can be seen on the emergency assessment sheets, CPPT, and resumes of discharged patients. The cause of the inaccuracy of the code on the emergency assessment sheet had not been clearly written down on the chronology of events and blank sheets were still found. For encoding, it has reached the 5th character.